Causes of Discrepancies in Value Estimates on Compensation for Oil Spill Damages in the Niger Delta - Michael Ayodele Olukolajo (Journal of African Real Estate Research, 2020)
This study examines causes of discrepancies in valuers’ opinion when determining monetary compensation payable to claimants for oil spill related damages in the Niger Delta, Nigeria. The study elicited data on factors responsible for differences in opinion of compensation values from valuers in practicing firms in Niger Delta using survey questionnaire. Eighty-three (83) Estate Surveying and Valuation (ESV) firms participated in the survey. The sample was selected from the total population of 190 ESV firms in the region based on the evidence of their experience with oil spill compensation valuation. Weighted mean score and factor analysis were employed in the data analysis. Results indicated that the factors causing discrepancies are: weak standards/codes of practice, inadequate legal frameworks, gaps in valuers’ knowledge, and professional misconduct. It was recommended that a specific code of practice for compensation for oil spill damage be developed by the Estate Surveyors and Valuers Registration Board of Nigeria (ESVARBON) in collaboration with the Nigerian Institution of Estate Surveyors and Valuers (NIESV) to guide valuers when undertaking valuation for compensation for damages arising from oil spills.